Pengaruh Penambahan Tepung Kepala Udang Dalam Pakan Terhadap Pigmentasi Warna Pada Ikan Koi (Cyprinuscarpiolynn) Jenis Kohaku - Niken Puspita Sari; Limin Santoso; Siti Hudaidah (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
Koi as ornamental fish excellence in body shapes with interesting colour. Chromatopore cells took responsibility to colour of fish. Enhancing of colour possible with added of carotenoid source like shrimp head meal in feed. This study purposes to assessed effects of shrimp head meal to enhance colour of koi in different percentages of inclusion (0, 10, 12 and 14 %). Koi in juvenile size, 3 month old, 28 g of body weight and 12 cm of total length used for this study. Five trained persons by used Toca Colour Finder (TCF) justified  scores of colour patterns during 60 days of culture. Results showed 10 % inclusion of shrimp head meal optimum in carotenoid those effect to enhances of colour. Positive corelation showed between amount of chromatopore cells and percentage of inclusion of shrimp head meal.